ANALISIS TEMATIK HADIS HIJAMAH DAN RELEVANSINYA DALAM DAKWAH KONTEMPORER BERBASIS KESEHATAN - M. Fatchurrohman; Ngatmin Abbas; Elvi Na`'imah (LPPM STAI Muhammadiyah Probolinggo, 2026)
Hijamah (cupping therapy) is a traditional medical practice strongly rooted in the prophetic traditions (hadith) and forms part of prophetic medicine (ṭibb al-nabawī). However, in modern society, hijamah is often understood partially, either as a cultural tradition or as an alternative therapy without comprehensive scientific grounding. Therefore, this study aims to examine the hadiths related to hijamah using a thematic (maudhu’i) approach and to analyze its relevance in contemporary da'wah. This research employs a qualitative method with a library research design, utilizing primary sources from classical hadith collections and relevant academic literature. Data analysis includes hadith inventory, sanad and matan analysis, and contextual interpretation. The findings reveal that most hadiths on hijamah are classified as authentic (ṣaḥīḥ) and good (ḥasan), containing health-related messages that are preventive, curative, and holistic. Furthermore, hijamah demonstrates compatibility with modern scientific findings in the medical field. From a da'wah perspective, hijamah can be developed as a form of da'wah bil-ḥāl, offering an integrative, practical, and solution-oriented approach. The significance of this study lies in its contribution to integrating hadith studies and da'wah while proposing a health-based da'wah model that is relevant to contemporary society.